Relationship between soil management and rainfall erosion: A case study in the Guajará-Mirim river watershed, Vigia - Pará - Goes, Jaime Carvalho; Oliveira, Eder Silva de (International Journal of Advanced Engineering Research and Science, 2022)
This study aims to evaluate the relationship between soil management and its loss by rainfall erosion in the watershed of the Guajará-Mirim river. The methodology used was essentially carried out by remote sensing, literature review and the application of the Universal Soil Loss Equation (USLE), with the geoprocessing of matrix and vector files in the QGIS software. The results show that, in relation to soil management in the study region, considering that it is a plain and that there were no measures to control soil erosion, its loss by rainwater transport is aggravated the greater the exposure of the soil, that is, the removal of vegetation and the revolving soil horizons. This assertion is evidenced by the greater soil loss in the areas mapped for sand extraction and deforestation by calculating the Universal Soil Loss Equation.